Influence of soil aeration status on denitrifier gene expression and denitrification gas fluxes (N2O and N2) from repacked pasture soils - Juan Liu; Timothy Clough; Sam Carrick; Jiafa Luo; Andriy Podolyan; Naomi Wells; Jupei Shen; Peng Li; Lianfeng Du; Hong Pan; Limei Zhang; Qiang Zhang; et al. (Soil Biology and Biochemistry, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

How to estimate age of old bottlenose dolphins (Tursiops truncatus); by tooth or pectoral flipper? - Ashley Barratclough; Wayne E. McFee; Megan Stolen; Aleta A. Hohn; Gretchen N. Lovewell; Forrest M. Gomez; Cynthia R. Smith; Daniel Garcia-Parraga; Randall S. Wells; Celeste Parry; Risa Daniels; Sam H. Ridgway; et al. (Frontiers in Marine Science, 2023)
Multiple techniques have been used for estimating age in bottlenose dolphins ( Tursiops truncatus ). The longest established technique is via counts of growth later groups (GLGs) in the longitudinal section of an extracted mandibular tooth. Previous studies to validate GLGs have primarily used younger dolphins (less than 16yrs old) due to the limited number of known age older animals. This study assessed the accuracy of age estimates for bottlenose dolphins using both GLG analysis and a newer technique, pectoral flipper radiography (PFR) for dolphins ranging from 0 to 58yrs, with a majority of samples (70%) over 16yrs. GLGs were assessed by two expert independent readers on tooth sections from 52 different dolphins (85% over 16yrs, maximum age 58yrs), and assessments of PFRs were performed by two experienced veterinarians on 37 dolphins (54% over 16yrs, maximum age 54yrs). Results demonstrated both techniques became less accurate in older dolphins, particularly those > 30yrs, with errors as large as 37yrs for GLG estimates. The root mean squared error (RMSE) for age estimation using GLGs for dolphins ≤15 years of age was 1.46yrs compared to 1.58yrs using PFRs demonstrating the accuracy of both techniques in this age bracket. For dolphins >30yrs, RMSE increased to 17yrs in GLG aging and 8.25yrs in PFR. Challenges in obtaining accurate age estimates in GLGs were primarily due to sectioning and staining difficulties in visualizing the newest GLG layers, in the very old animals. Complications in reading the layers included obtaining a good section, the presence of accessory layers, GLG compression, and tooth curvature or wear removing the neonatal line influencing aging biases. In pectoral flipper aging, the primary challenge was obtaining a true dorsoventral radiograph in a live dolphin during a health assessment, as well as the subjective assessment of scoring and reliance on degenerative changes accurately estimate age in geriatric dolphins. While access to the radiography equipment can be a limiting factor, the improved accuracy for age estimation in adult dolphins, the less invasive nature, and reduced processing time to results make pectoral radiography a preferred alternative technique for estimating age in live dolphins.

Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Walter Dellisanti; Jeffery T. H. Chung; Sam K. F. Yiu; Ryan Ho Leung Tsang; Put Ang; Yip Hung Yeung; Jian-Wen Qiu; Shelby E. McIlroy; Mark L. Wells; Jiajun Wu; Leo Lei Chan (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean < 31°C) but reduced the energetic productivity of corals (-44% relative to winter). Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification (+20% relative to summer). Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.

Unifying biological field observations to detect and compare ocean acidification impacts across marine species and ecosystems: what to monitor and why - Steve Widdicombe; Kirsten Isensee; Yuri Artioli; Juan Diego Gaitán-Espitia; Claudine Hauri; Janet A. Newton; Mark Wells; Sam Dupont (Ocean Science, 2023)
Approximately one-quarter of the CO2 emitted to the atmosphere annually from human activities is absorbed by the ocean, resulting in a reduction of seawater pH and shifts in seawater carbonate chemistry. This multi-decadal process, termed “anthropogenic ocean acidification” (OA), has been shown to have detrimental impacts on marine ecosystems. Recent years have seen a globally coordinated effort to measure the changes in seawater chemistry caused by OA, with best practices now available for these measurements. In contrast to these substantial advances in observing physicochemical changes due to OA, quantifying their biological consequences remains challenging, especially from in situ observations under real-world conditions. Results from 2 decades of controlled laboratory experiments on OA have given insight into the likely processes and mechanisms by which elevated CO2 levels affect biological process, but the manifestation of these process across a plethora of natural situations has yet to be fully explored. This challenge requires us to identify a set of fundamental biological and ecological indicators that are (i) relevant across all marine ecosystems, (ii) have a strongly demonstrated link to OA, and (iii) have implications for ocean health and the provision of ecosystem services with impacts on local marine management strategies and economies. This paper draws on the understanding of biological impacts provided by the wealth of previous experiments, as well as the findings of recent meta-analyses, to propose five broad classes of biological indicators that, when coupled with environmental observations including carbonate chemistry, would allow the rate and severity of biological change in response to OA to be observed and compared. These broad indicators are applicable to different ecological systems, and the methods for data analysis suggested here would allow researchers to combine biological response data across regional and global scales by correlating rates of biological change with the rate of change in carbonate chemistry parameters. Moreover, a method using laboratory observation to design an optimal observing strategy (frequency and duration) and observe meaningful biological rates of change highlights the factors that need to be considered when applying our proposed observation strategy. This innovative observing methodology allows inclusion of a wide diversity of marine ecosystems in regional and global assessments and has the potential to increase the contribution of OA observations from countries with developing OA science capacity.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Sustainability-oriented learning: evidence from Eyre Peninsula’s fishing industry in Australia - Samuel Howard Quartey; Sam Wells (Environment, Development and Sustainability, 2020)

Regional engagement and spatial modelling for natural resource management planning - Wayne S. Meyer; Brett A. Bryan; David M. Summers; Greg Lyle; Sam Wells; Josie McLean; Mark Siebentritt (Sustainability Science, 2016)

Individual specialization in the foraging habits of female bottlenose dolphins living in a trophically diverse and habitat rich estuary - Sam Rossman; Peggy H. Ostrom; Megan Stolen; Nélio B. Barros; Hasand Gandhi; Craig A. Stricker; Randall S. Wells (Oecologia, 2015)

Foraging habits in a generalist predator: Sex and age influence habitat selection and resource use among bottlenose dolphins ( Tursiops truncatus ) - Sam Rossman; Elizabeth Berens McCabe; Nélio B. Barros; Hasand Gandhi; Peggy H. Ostrom; Craig A. Stricker; Randall S. Wells (Marine Mammal Science, 2015)
This study examines resource use (diet, habitat use, and trophic level) within and among demographic groups (males, females, and juveniles) of bottlenose dolphins ( Tursiops truncatus ). We analyzed the δ 13 C and δ 15 N values of 15 prey species constituting 84% of the species found in stomach contents. We used these data to establish a trophic enrichment factor ( TEF ) to inform dietary analysis using a Bayesian isotope mixing model. We document a TEF of 0‰ and 2.0‰ for δ 13 C and δ 15 N, respectively. The dietary results showed that all demographic groups relied heavily on low trophic level seagrass‐associated prey. Bayesian standard ellipse areas ( SEA b ) were calculated to assess diversity in resource use. The SEA b of females was nearly four times larger than that of males indicating varied resource use, likely a consequence of small home ranges and habitat specialization. Juveniles possessed an intermediate SEA b , generally feeding at a lower trophic level compared to females, potentially an effect of natal philopatry and immature foraging skills. The small SEA b of males reflects a high degree of specialization on seagrass associated prey. Patterns in resource use by the demographic groups are likely linked to differences in the relative importance of social and ecological factors.

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Retrospective analysis of bottlenose dolphin foraging: A legacy of anthropogenic ecosystem disturbance - Sam Rossman; Nélio B. Barros; Peggy H. Ostrom; Craig A. Stricker; Aleta A. Hohn; Hasand Gandhi; Randall S. Wells (Marine Mammal Science, 2013)
We used stable isotope analysis to investigate the foraging ecology of coastal bottlenose dolphins ( Tursiops truncatus ) in relation to a series of anthropogenic disturbances. We first demonstrated that stable isotopes are a faithful indicator of habitat use by comparing muscle isotope values to behavioral foraging data from the same individuals. δ 13 C values increased, while δ 34 S and δ 15 N values decreased with the percentage of feeding observations in seagrass habitat. We then utilized stable isotope values of muscle to assess temporal variation in foraging habitat from 1991 to 2010 and collagen from tooth crown tips to assess the time period 1944 to 2007. From 1991 to 2010, δ 13 C values of muscle decreased while δ 34 S values increased indicating reduced utilization of seagrass habitat. From 1944 to 1989 δ 13 C values of the crown tip declined significantly, likely due to a reduction in the coverage of seagrass habitat and δ 15 N values significantly increased, a trend we attribute to nutrient loading from a rapidly increasing human population. Our results demonstrate the utility of using marine mammal foraging habits to retrospectively assess the extent to which anthropogenic disturbance impacts coastal food webs.

Establishment and quantitative imaging of a 3D lung organotypic model of mammary tumor outgrowth - Michelle D. Martin; Barbara Fingleton; Conor C. Lynch; Sam Wells; J. Oliver McIntyre; David W. Piston; Lynn M. Matrisian (Clinical & Experimental Metastasis, 2008)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)